Early Childhood Education and Its Correlation with Crime: A Review - Anwar Anwar; Tatum Derin (Utamax : Journal of Ultimate Research and Trends in Education, 2019)
This article reviews the new evidence offered by Jorge Luis García, James J. Heckman and Anna L. Ziff's paper entitled "Early Childhood Education and Crime." The paper showcased the impact of crime reduction from high-quality intensive early childhood programs. Its distinct advantage from other similar research attempts is it's long-term follow-up. The data collected were evaluated by randomized controlled trials, and this present article is interested in reviewing the results using a descriptive qualitative method. It is found, proportionally, more women than men reduce their criminal activities after participating in this program. Gender influences the experiences, giving a difference because the home environment of disadvantaged families that are mainly benefited by this program is typically worse for girls. This program of educating children with the particular purpose of shaping their morality and understanding of good and bad gives a suitable scope for better improvement by the program. For both sexes, the effect of treatment is greater for disadvantaged children, as measured by the education given by their mothers.